THE INFLUENCE OF LITERARY TRANSLATION IN THE CREATION OF THE IMAGE OF THE HORSE - Soibova Gulchiroy Baxtiyorjon qizi (International Journal of Literature and Language Studies, 2026)
This study explores the influence of literary translation on the representation of the horse image in English and Uzbek literary traditions. The findings reveal that while English literary tradition primarily portrays the horse as a symbol of freedom, individuality, and resistance to cruelty, Uzbek literature emphasizes loyalty, honor, collective identity, and spiritual continuity. The research demonstrates that successful literary translation requires not only linguistic accuracy but also the preservation of cultural symbolism and emotional impact. The horse image serves as an important intercultural marker reflecting national values, historical experience, and ethical ideals in both literary traditions.